2011
DOI: 10.4103/0970-2113.80314
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary functions in patients with diabetes mellitus

Abstract: Background:A reduction in lung capacity has been reported previously among diabetics. According to WHO estimates, Pakistan is currently eighth in the prevalence of diabetes mellitus (DM) and will become fourth by the year 2025 with over 15 million individuals. This study was designed to see the impairment of lung functions on spirometry in DM patients.Objective:Our aim was to investigate the pulmonary functions tests of Pakistani patients with DM.Materials and Methods:Between January to July 2004, 128 subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
33
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 20 publications
9
33
2
1
Order By: Relevance
“…However there was mild reduction in FEV1/FVC which was not statistically significant. The findings were similar to those reported by Irfan et al and Klein et al 5,6 Study conducted by Davis et al also demonstrated that VC, FVC, FEV1 and PEF were decreased in type 2 diabetic patients. 9 Non enzymatic glycosylation induced alteration of lung connective tissue is one of the most likely underlying mechanism which is being investigated for restrictive lung disorder.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However there was mild reduction in FEV1/FVC which was not statistically significant. The findings were similar to those reported by Irfan et al and Klein et al 5,6 Study conducted by Davis et al also demonstrated that VC, FVC, FEV1 and PEF were decreased in type 2 diabetic patients. 9 Non enzymatic glycosylation induced alteration of lung connective tissue is one of the most likely underlying mechanism which is being investigated for restrictive lung disorder.…”
Section: Discussionsupporting
confidence: 82%
“…This is similar to the study published by Irfan M et al where the mean age was 54.3. 5 The proportion of females was 42% (n = 21) in the study group and 44% (n = 22) in the control group. The mean Body Mass Index of the study group was 23.88±3.47 kg/m 2 and the control group was 23.27±4.27kg/m 2 , (P = 0.4388).…”
Section: Discussionmentioning
confidence: 99%
“…40 percent female with diabetes mellitus [16]. Another study by Irfan et al [17] published on 2011 has taken 42 percent of female with diabetes showing similar group division as in our study.…”
Section: Discussionsupporting
confidence: 70%
“…"Pulmonary function test in type 2 diabetes mellitus and their association with glycemic control and duration of diabetes mellitus" a study by Shah et al [18] also has taken a subject with mean age of 53.90± 8.45 Vs 54.88±8.28 among diabetic and non diabetics. Other study by Zeneldin et al [19] published in 2015 and Irfan et al also had higher mean age among the control subjects [17]. Anandhalakshmi S et al [20] and El-Habashy MM et al (2013) [21] scrutinized that in both diabetic and non-diabetic group mean age of the patients was younger (44.8± 8.9 vs. 39.4 ± 11.7), due to small sample size these studies showed dissimilar results.…”
Section: Discussionmentioning
confidence: 91%
“…Vorangegangene Studien zeigten, dass kardiovaskuläre Risikofaktoren sowohl bei Rauchern als auch bei Nichtrauchern in Verbindung mit Verände-rungen der Lungenfunktion stehen kön-nen. So vermag die gestörte Glucosetoleranz ebenso wie der T2D mit einer pulmonalen Funktionseinschränkung einherzugehen [19,26,51]. Dabei konnte neben einer erhöhten Prävalenz von OLD eine Verringerung von FEV 1 und FVC bzw.…”
Section: Pulmonary Function In Elderly Subjects With Metabolic Syndrounclassified